Rizzoli & Isles Season 4 Disc 2 - Harmon, Angie, 1972-; Alexander, Sasha, 1973-; Bridges, Jordan, 1973-; Tamaro, Janet; Babbit, Jamie, 1970-; Peterson, Lisa Marie; Hanes, Ken; Cheylov, Milan; Holahan, Paul; Zisk, Randall; Warner Home Video (Firm) (Burbank, CA Warner Home Video, 2014)
Jane and Maura investigate a number of complex and troublesome cases, including a deadly shooting at a community parade, the brutal killing of an overzealous journalism student, and the pending murder trial of Maura's biological father, Paddy Doyle.
Dance with the devi l / teleplay by Janet Tamaro ; directed by Jamie Babbit -- Somebody's watching me / written by Lisa Marie Peterson & Ken Hanes ; directed by Milan Cheylov -- All for one / written by Janet Tamaro ; directed by Paul Holahan -- Cold as ice / written by Ken Hanes & Lisa Marie Peterson ; directed by Randy Zisk.
Originally broadcast as episodes 5-8 of season 4 of the television series in 2013.
Title from container and disc label.
Angie Harmon, Sasha Alexander, Jordan Bridges, Lee Thompson Young, Bruce McGill.
Rating: Not rated.
DVD, region 1, widescreen; Dolby digital 5.1; dual layer.
English dialogue; English or French; English subtitled for the deaf and hard of hearing.
Keywords: Isles, Maura -- (Fictitious character); Rizzoli, Jane, -- Detective (Fictitious character); Medical examiners (Law) -- Massachusetts -- Boston -- Drama; Women detectives -- Massachusetts -- Boston -- Drama; Forensic pathologists -- Massachusetts -- Boston -- Drama; Criminal investigation -- Massachusetts -- Boston -- Drama; Massachusetts -- Boston; Drama; Television cop shows; Television programs; Video recordings for the hearing impaired